Global Shift: Mapping the Changing Contours of the World Economy - Peter Dicken (Great Britain Sage, 2015)
Global Shift is - quite simply - the definitive work on economic globalization. The extensive use of graphics, lack of jargon, and clear definition of terms has made it the standard work for the social sciences. The Seventh Edition has been completely updated using the latest available sources. It maps the changing centres of gravity of the global economy and explains the global financial crisis. Each chapter has been extensively rewritten and new material introduced to explain the most recent empirical developments; ideas on production, distribution, consumption; and corporate governance. Global Shift provides: The most comprehensive and up-to-date explanation of economic globalization available, examining the role of transnational corporations, states, labour, consumers, organizations in civil society, and the power relations between them. A clear guide to how the global economy is being transformed through the operation of global production networks involving transnational corporations, states, interest groups and technology. Extended discussion of problems and institutions of global governance in the context of the global economic crisis and of the role of corporate social responsibility. A suite of extensive online ancillaries for both students and lecturers, including author videos, case studies, lecture notes, and free access to specially selected journal articles related to each chapter. There is only one definitive guide to economic globalization for the social sciences: and that's Peter Dicken's Global Shift.
Keywords: Economics; Nonfiction; Geography; Politics; Business; International relations; Sociology; Academic; Textbooks; International Business and Management (ECO2023-N )